Parameter Optımızatıon And Controller Desıgn For A Real Tıme Conıcal Tank System - S.K.Indumathi,N.Keerthika,K.Nageswara Rao,A.Thamarai Selvi,Dr.Uppu Ramachandraiah (International Journal of Advanced Science and Technology, 2020)
The process of controlling the level of liquid is the most important and mandatory in process based industries. Due to the presence of non-linearity and constantly varying cross sectional area, controlling the level of liquid becomes a challenging task. Most of the industries use tanks in conical shape as it is highly non-linear. It provides better discharge of slurries, solid mixtures and viscous liquids. The objective of the work is to develop a suitable controller and to analyse its performance in maintaining the tank with suitable level of liquid. In this work, a conical tank is considered for which the controller is designed by using PID and Fuzzy logic. The performance response of the controller developed based on PID and Fuzzy logic is studied, compared and analyzed